Translation peculiarities of collocations - Nematova M (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The importance of collocation in literary text arises from the fact that collocations are one of the fixed expressions that are used by authors or writers to express figurative meanings, traditions, religious beliefs ideology. This paper defines diverse features of translation of collocation. In this article there was given various ways of translating lexical units.